Relationship of ACE Gene Insertion/Deletion (I/D) Polymorphisms with Hearing Loss (HL) in Patients from Bahawalpur, Pakistan: Relation of ACE Gene with Hearing Loss (Biological Sciences - PJSIR, 2023)
Hearing loss (HL) is an inability to hear completely or partially. It can be permanent or temporary depending upon the causative factor involved. One of the factors is high blood pressure that can be responsible for hearing loss at any age. A gene named Angiotensin-Converting Enzyme (ACE) gene that has nearly the size of 21kb is located on the 17q 23 chromosome in humans. The purpose of this study was to determine if any association is present between ACE insertion/deletion (I/D) polymorphisms in hypertensive patients suffering from hearing loss.